N,N-Bis(2-hydroxyethyl)-4-methylbenzenesulfonamide - Mushtaq, Nafeesa (International Union of Crystallography, 2012)
In the title compound C(11)H(17)NO(4)S, an intramolecular O—H⋯O hydrogen bond forms an S(8) ring and determines the conformation of the bis(2-hydroxyethyl) segment of the molecule, holding the two CH(2)CH(2)OH groups close to coplanar (r.m.s. deviation = 0.185 Å). In the crystal, O—H⋯O hydrogen bonds link the molecules into zigzag chains along the b axis. Weaker additional C—H⋯O and C—H⋯π contacts generate a three dimensional network, with molecules stacked along the b-axis direction.